The role of administrative empowerment in improving the quality of collective performance - AL-Muttairi , Wafaa Majeed Jaber (South Asian Journal of Social Sciences and Humanities, 2025)
The study aimed to identify the degree of administrative empowerment represented by the dimensions (delegation of authority, training and learning, motivation, independence) among senior leaders in achieving university performance quality represented by (tangibility, reliability, credible responsiveness) at the University of Basra, in addition to the differences in the degree of administrative empowerment among college deans. To achieve this, the study was conducted on a sample of a group of senior leadership opinions in universities and colleges (head of department, department headquarters, head of units and divisions), and the (SPSS) program was used to process the data. Among the most important results reached by the study are: the study proved the existence of two main relationships between administrative empowerment and the quality of university performance at the university under study: a correlation relationship and an influence relationship. Also, in terms of impact, the results showed that administrative empowerment has a direct and positive impact on the quality of university performance.